(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This article, based on published sources, tries to present the Croatian history of the second half of the 20th century in a European context. It should be pointed out that the communist regime of the Socialist Federal Republic of Yugoslavia (SFRJ), and thus the Socialist Republic of Croatia (SRH) in the period 1945-1990 causes various controversies, therefore also about whether it is a totalitarian or authoritarian regime. As part of these considerations, published sources such as: books, anthologies, scientific articles, testimonies of participants of the time and events, periodicals and films were primarily used. Equally, for the purposes of the article, unpublished archive material of the Yugoslav communist regime, State Security Service (SDS) for the observed period was also consulted.